Study on Compaction Characteristics and Construction Control of Mixtures of Red Clay and Gravel - Biao Zeng; Lin-feng Wang; Yun Tian; Tao-rui Zeng; Bing Li (Advances in Civil Engineering)
Red clay cannot be used as embankment filler directly due to its water-sensitive property. Gravel is usually added into red clay to enhance its performance in engineering practice. In order to investigate the influence of mixtures of red clay and gravel on the road performance, gravitational compaction experiment of red clay and vibratory compaction experiment of mixtures of red clay and gravel were conducted, respectively. The results indicate that compaction curves of red clay have double peak; the second peak is the real maximum dry density, and its corresponding moisture content is the optimal moisture content. The dry density of mixtures of red clay and gravel is influenced by the content of gravel, vibration frequency, and vibration time. The optimal content of gravel is 30%, the best vibration frequency is 45 Hz, and the optimal vibration time is 5 minutes for the mixtures of red clay and gravel in this study. The effectiveness of optimal content of gravel and optimum vibration parameters was confirmed by a CBR test. According to the compaction experiment results and actual situation in the field, a suitable construction method of subgrade using the mixtures of red clay and gravel was put forward. The feasibility of this method was also confirmed by postconstruction deformation data of the field test embankment.